Thermal annealing impact on optical properties of spin-coated P3HT: CdS thin film - Zakaria, Nabila Anis; Mohd Azmi, Mohd Syahriman; Naning @ Zin, Fatin Hana; Capan, Rifat; Syed Mohamad, Syed Abdul Malik (Faculty of Science and Mathematics, Universiti Pendidikan Sultan Idris, 2023)
Polymers are flexible materials that can be easily processed and are formed into a thin film by several methods such as spin-coating, dip-coating, film-casting, and printing. The spin coating method has been extensively utilized in fabricating solution-prepared organic/inorganic electronic devices, this technique is positively efficient in generating thin film apart from being a flexible method to execute. In this study, poly(3-hexylthiophene) (P3HT) material is selected as polymer and cadmium sulphide (CdS) as nanoparticles to produce a hybrid nanocomposite thin film through the process spin-coating method. The P3HT and cadmium ion solution were used to fabricate a thin film onto a quartz glass substrate at a spin speed of 500 rpm for 10 seconds. This spin-coated thin film was heated at different temperatures such as 40°C, 80°C, 120°C, and 160°C for optical properties using a UV-Vis spectrophotometer. The UV-Vis absorption spectra of P3HT: CdS indicated absorption peaks in the UV region, which were ascribed to the band gap of the P3HT: CdS thin film. Our results showed that the optical properties of the P3HT: CdS be contingent on the annealing temperature. The film at room temperature yielded a band gap value of 1.98 eV, at 40°C it resulted in 1.99 eV. The band gap value was increased when annealed at 80°C with 2.02eV. Annealing temperatures were then raised to 120°C and 160°C, leading to band gap values of 3.11 eV and 2.80 eV respectively.